ChemInform Abstract: Luminescence Properties of Ca3Ti2O7:Eu3+, Bi3+, R+ (R+: Li+, Na+, and K+) Red Emission Phosphor. Issue 45 (23rd October 2014) - Cao, Renping; Chen, Guo; Yu, Xiaoguang; Cao, Chunyan; Chen, Kangbin; Liu, Pan; Jiang, Shenhua
Abstract The title phosphors are prepared by solid state reaction using CaCO3, M2CO3 (M: Li, Na, K), TiO2, Eu2O3, and Bi2O3 as source materials (600 °C for 5 h and 1350 °C for 4 h in air).